Prevalence of signs of trachoma, ocular Chlamydia trachomatis infection and antibodies to Pgp3 in residents of Kiritimati Island, Kiribati. - Anaseini Cama; Andreas Müller; Raebwebwe Taoaba; Robert M R Butcher; Iakoba Itibita; Stephanie J Migchelsen; Tokoriri Kiauea; Harry Pickering; Rebecca Willis; Chrissy H Roberts; Ana Bakhtiari; Richard T Le Mesurier; et al. (Public Library of Science (PLoS), 2017)
In some Pacific Island countries, such as Solomon Islands and Fiji, active trachoma is common, but ocular Chlamydia trachomatis (Ct) infection and trachomatous trichiasis (TT) are rare. On Tarawa, the most populous Kiribati island, both the active trachoma sign "trachomatous inflammation-follicular" (TF) and TT are present at prevalences warranting intervention. We sought to estimate prevalences of TF, TT, ocular Ct infection, and anti-Ct antibodies on Kiritimati Island, Kiribati, to assess local relationships between these parameters, and to help determine the need for interventions against trachoma on Kiribati islands other than Tarawa.As part of the Global Trachoma Mapping Project (GTMP), on Kiritimati, we examined 406 children aged 1-9 years for active trachoma. We collected conjunctival swabs (for droplet digital PCR against Ct plasmid targets) from 1-9-year-olds with active trachoma, and a systematic selection of 1-9-year-olds without active trachoma. We collected dried blood spots (for anti-Pgp3 ELISA) from all 1-9-year-old children. We also examined 416 adults aged ≥15 years for TT. Prevalence of TF and TT was adjusted for age (TF) or age and gender (TT) in five-year age bands.The age-adjusted prevalence of TF in 1-9-year-olds was 28% (95% confidence interval [CI]: 24-35). The age- and gender-adjusted prevalence of TT in those aged ≥15 years was 0.2% (95% CI: 0.1-0.3%). Twenty-six (13.5%) of 193 swabs from children without active trachoma, and 58 (49.2%) of 118 swabs from children with active trachoma were positive for Ct DNA. Two hundred and ten (53%) of 397 children had anti-Pgp3 antibodies. Both infection (p<0.0001) and seropositivity (p<0.0001) were strongly associated with active trachoma. In 1-9-year-olds, the prevalence of anti-Pgp3 antibodies rose steeply with age.Trachoma presents a public health problem on Kiritimati, where the high prevalence of ocular Ct infection and rapid increase in seropositivity with age suggest intense Ct transmission amongst young children. Interventions are required here to prevent future blindness.